Co-occurrence of Dinophysis tripos and pectenotoxins in Argentinean shelf waters - Fabro Cerreia Fus, Elena Inés (2015)
The species Dinophysis tripos is a widely distributed marine dinoflagellate associated with diarrheic shellfish poisoning (DSP) events, which has been recently identified as a pectenotoxin (PTX) producer. In two sampling expeditions carried out during austral autumns 2012 and 2013 along the Argentine Sea (≈38–56° S), lipophilic phycotoxins were measured by tandem mass spectrometry coupled to liquid chromatography (LC–MS/MS) in size-fractionated plankton samples together with microscopic analyses of potentially toxic phytoplankton. PTX-2, PTX-11 and PTX-2sa were recurrently detected in the 50–200 μm fractions, in association to D. tripos. PTX-2 was also widely distributed among the 20–50 μm fractions, mostly related to Dinophysis acuminata. Okadaic acid or its analogs were not detected in any sample. This is the first report of D. tripos related to PTX in the Argentine Sea and the first record of PTX-11 and PTX-2sa for this area. The morphological variability of D. tripos, including the presence of intermediate, small and dimorphic cells, is described. Also, the micro- and mesoplanktonic potential grazers of Dinophysis spp. were explored.